Adipose‐derived exosomes: A novel adipokine in obesity‐associated diabetes. Issue 10 (26th February 2019) - Zhang, Bo; Yang, Yang; Xiang, Lin; Zhao, Zhihe; Ye, Rui
Abstract: Dysfunction of the adipose tissue is a central driver for obesity‐associated diabetes. It is characterized by dysregulated adipokine secretion, which contributes to insulin resistance of key metabolic tissues, including the liver, skeletal muscles, and fat itself. The inter‐organ cross talk between the adipose tissue and the other organs as well as the intra‐organ cross talk between adipocytes and macrophages within the adipose tissue, traditionally mediated by hormones, was recently evidenced to be regulated by adipose‐derived exosomes. Exosomes are nano‐sized membrane‐bound vesicles secreted by the donor cells to modify intercellular communication by translating constituent nucleic acids and proteins to the target cells. Herein, we reviewed the latest progress in understanding the role of adipose‐derived exosomes in the development of insulin resistance, a key mechanism that underpins diabetes and diabetic complications,  with a special focus on the role of exosomal miRNAs (micro RNAs) and proteins,  and discusses the potential implications of targeting adipose tissue‐derived exosomes for diabetic therapeutics. Abstract : Dysfunction of the adipose tissue is a central driver for obesity‐associated diabetes. Herein, we reviewed the latest progress in understanding the role of adipose‐derived exosomes in the development of insulin resistance, a key mechanism that underpins diabetes and diabetic complications, with a special focus on the role of exosomal miRNAs (micro RNAs) and proteins, and discuss the potential implications of targeting adipose tissue‐derived exosomes for diabetic therapeutics.